Electron-induced modification of self-assembled monolayers of aromatic carboxylic acids - Asyuda, Andika; Ortiz de la Morena, Rodrigo; Sauter, Eric; Turner, Kelly; McDonald, Kirsty; Buck, Manfred; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2020)
The effects of low-energy electrons on aromatic self-assembled monolayers (SAMs) with carboxylic acid (CA) docking groups were studied with a focus on the dose range below 5 mC/cm2. The SAMs were prepared on an underpotentially deposited Ag bilayer and comprised nonsubstituted and CA-substituted monolayers with a rod-like biphenyl backbone and a monolayer of a Y-shaped, CA-substituted molecule, 1,3,5-benzenetribenzoic acid (H3BTB), formed either as a single-component film or as a binary one by mixing with adamantane-CA (Ad-CA). X-ray photoelectron and near-edge X-ray absorption fine structure spectra suggest high proneness of the CA groups to electron irradiation at both SAM/substrate and SAM/ambient interfaces. Cleavage of the carboxylate-substrate bond results in substantial molecular desorption at the initial stage of irradiation until electron-induced cross-linking gradually takes over. The CA groups at the outer SAM interface undergo substantial chemical changes, indicating that they participate in the cross-linking chemistry. The electron-induced processes are accompanied by molecular reorientation. Disordering for the SAMs formed by the rod-like molecules is contrasted by the H3BTB-based systems where changes also occur but some molecular order is preserved as explained by a proposed model invoking conformational changes. In SAMs of H3BTB mixed with Ad-CA, the latter shows higher proneness to irradiation-induced desorption than the former, as well as an influence on the cross-linking chemistry. The results of the present study suggest that CA-based SAMs on Ag offer additional options for cross-linking in SAMs and, as exemplarily demonstrated by the generation of Cu patterns on structured H3BTB templates, can be efficiently used for lithography and nanofabrication